(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In this study, the methodological basis for assessing the state of digital development of human capital at the national level has been improved. The proposed evaluation methodology of the digital development of human capital is the DigTech (Digital technology) index, which allows to assess the country’s digital activity as a condition for the use of human capital, and the DigSoc (Digitalization of the social sphere) index to assess the level of digitization of the social sphere, which contributes to the digital development of human capital (culture, health indicators describing the digitization of the preservation and education sectors), as an indicator of the digital development of human capital, the DigKnow (Digital knowledge) index is based on a combination of three major indexes to assess the digital knowledge and skills of the country’s population. The developed methodology for evaluating the digital development of human capital at the national level allows for the quantitative assessment of the quality of human capital and the implementation of measures aimed at the formation and development of human capital and increasing the competitiveness of human capital in the digital economy.